Comprehensive evaluation of new sorghum varieties and their light-simple and efficient production technology: a case study of Ji Niang No. 2 - Liu, Meng; Liu, Huijing; Zhang, Han; Zhao, Wenqing; Zhao, Yu; Zheng, Zhi; Li, Shunguo (Frontiers in Agronomy, 2025)
The revitalization of the seed industry is of increasing significance in ensuring food security and promoting the high-quality development of modern agriculture. A series of superior sorghum varieties have been cultivated in China with the support of the National Technical System of Millet & Sorghum Industry to promote the high-quality development of the sorghum industry. In this paper, Ji Niang No. 2, the major achievement of the National Technical System of Millet & Sorghum Industry, is taken as the research object. Based on the field survey data in North China in 2023, STEM systematic evaluation method was adopted to evaluate Ji Niang No.2 and its supporting planting technology comprehensively. The results show that the comprehensive score of Ji Niang No. 2 and its supporting light-simple and efficient production technology is 85 points which accounts for 85%, making the whole promotion feasible. Specifically, it is scientifically feasible, due to its significant increase of planting area during a long promotion period, all-round and multi-level project support, excellent achievement accumulation. It is technically feasible because of its remarkable demonstration performance. It is economically feasible because of its remarkable effect of yield increase, revenue increase, water saving and fertilizer saving. It is feasible in terms of model both farmers and agricultural management departments give a high evaluation to Ji Niang No. 2 planting mode. Based on these findings, recommendations are proposed to support government policy formulation, benefiting not only China’s sorghum industry but also expanding to other countries worldwide.